THE CONCEPT OF ENVIRONMENT IN ISLAMIC EDUCATION AND ITS ROLE IN CHARACTER FORMATION OF STUDENTS - Winny Khodijah; Ummi Syarifah Auliyah; Muhammad Darwis Dasopang; Irwandi Sihombing (STMIK Indonesia Banda Aceh, 2026)
The environment is a fundamental factor in the Islamic education process because it directly influences the formation of students' character and personality. Islamic education takes place not only in the classroom but also through social interactions, culture, and the spiritual environment surrounding students. This article aims to analyze the concept of the environment from an Islamic educational perspective and its role in the formation of students' character. This research uses a qualitative method with a library research approach, examining primary and secondary sources in the form of the Qur'an, hadith, and the works of Islamic scholars and education experts. The results of the study indicate that the educational environment in Islam encompasses the family, school, community, and physical environment, all of which play a synergistic role in shaping Islamic morality. The family environment functions as the first madrasah (Islamic school), the school as a formal institution for fostering values, and the community as a social space for the actualization of Islamic values. In the digital era, environmental challenges are increasingly complex, necessitating the integration of digital literacy and the strengthening of Islamic values. Thus, optimizing the role of the educational environment is key to successfully forming the character of students with noble morals.